Plasma Cleaning of Metallic Mirrors from Carbon-Containing Films – New Possibilities for In Situ Monitoring of the Efficiency of Wall Conditioning in Fusion Devices - Voitsenya, V.S.; Konovalov, V.G.; Timoshenko, A.I.; Solodovchenko, S.I.; Ryzhkov, I.V.; Shtan, A.F.; Shapoval, A.N. (Journal of Coating Science and Technology, 2019)
The method proposed for measuring the erosion rate of the carbon film, pre-deposited on the mirror-like surface of the test metallic samples, directly during wall conditioning procedures in a fusion device. The practical realization of the method provided at the DSM-2 stand where deuterium plasma produced in conditions of electron resonance at frequency 2.45 GHz used for cleaning the samples. For controlling C-film thickness the time variation of electrical conductivity of the circuit ‘film+plasma+entire scheme’ was measured. The final cleaning stage sets according to the saturation section corresponding to the resistance of the entire measuring scheme. To check the state of full purification of samples from a carbon-containing film the reflectance at normal incidence in the wavelength 220-650 nm was measured before C-film deposition, just after C-film deposition, and after finishing the cleaning procedure. In all cases (16 experiments) the approach of total resistance to the ‘entire resistance’ of the scheme in use was supported by restoration of the reflectance of stainless steel samples to its initial value. The method can be reversed, i.e. allows one to control in situ the appearance of a contaminating layer growing on the surface of a metal sample, preliminary cleaned before being installed in a vacuum vessel